ANALYSIS OF BREEDERS' KNOWLEDGE LEVEL ON CATTLE ESTROUS PERIOD IN BUNTU BATU DISTRICT, ENREKANG REGENCY - DK, Taufik; Mufassir, Mufassir; Sukoco, Hendro; Wahyuni, Sri; Utami, Sri; Siswanto, Ferbian Milas (Agros Journal of Agriculture Science, 2023)
This study aimed to determine the breeders' knowledge level on cattle estrous  period in buntu batu district, enrekang regency. The type of research used is descriptive quantitative research, which is a type of research that describes the level of knowledge of breeders in knowing the breeding period of female cows in Buntu Batu District, Enrekang Regency. This research was conducted in Buntu Batu District, Enrekang Regency, South Sulawesi from January to April 2022. The population in this study were all cattle breeders in Buntu Batu District, Enrekang Regency. The sample in this study totaled 92 respondents in Buntu Batu District. Data collection consisted of primary and secondary data. Primary data was obtained by direct observation. While secondary data was taken from the Enrekang Livestock Service Office. Data were analyzed using descriptive methods for the overall data in presenting frequency distribution tables. The results of the research analyzed the level of knowledge of breeders on the breeding period of cattle is enoug with a total of 41.3%.Keywords : Cattle, Estrous, Knowledge Of Breeders, Enrekang